2013
DOI: 10.1149/2.094308jes
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Capacitive Deionization Utilizing Low Surface Area Carbon Electrodes Coated with Nanoporous Thin-Films of Al2O3and SiO2

Abstract: Capacitive deionization (CDI) has recently gained some degree of popularity as a water treatment technology. This paper demonstrates the benefits of coating low surface area carbon electrodes with a sub-micron nanoporous layer of either γ-Al2O3 or SiO2. As shown by cyclic voltammetry, the oxide layer, having pores sizes ranging from larger micro to meso, substantially increased capacitance for ion removal while still maintaining reasonably high ohmic conductivity. The amount of Ca2+ removed in a CDI cell compr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
38
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 42 publications
3
38
1
Order By: Relevance
“…The carbon support used in this work was chosen because of its high surface area, relatively cheap cost and availability. Thus, this material, unlike other metal-oxide coated composites described elsewhere [15][16][17][18], has a surface area over 1200 m 2 g À1 . Finally, most of the work in CDI has focused on desalination/brackish water treatment [22,23], making NaCl solutions the most studied systems [7][8][9]14,21,24,25].…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations
“…The carbon support used in this work was chosen because of its high surface area, relatively cheap cost and availability. Thus, this material, unlike other metal-oxide coated composites described elsewhere [15][16][17][18], has a surface area over 1200 m 2 g À1 . Finally, most of the work in CDI has focused on desalination/brackish water treatment [22,23], making NaCl solutions the most studied systems [7][8][9]14,21,24,25].…”
Section: Introductionmentioning
confidence: 93%
“…The specific surface area was calculated from the BET equation using relative pressures in the data range between 0.06 and 0.2. The PSD was determined by fitting theoretical adsorption isotherms based on the DFT model, which produced the fit with the smallest standard deviation [17]. The quantity of metal oxide that had been deposited on the substrate was determined by thermo-gravimetric analysis using a Mettler Toledo TGA/SDTA851e device, following a methodology previously described [17].…”
Section: Electrode Preparation and Characterizationmentioning
confidence: 99%
See 2 more Smart Citations
“…These imbalances have been used to selectively remove ions from solution [21,[28][29][30], but could adversely affect the equilibrium salt adsorption capacity of a CDI cell. A recent study reported that the effect of asymmetry in anode and cathode geometric ratios (where anode was 2x and 3x times larger than the cathode and vice-versa) led to an increased salt adsorption capacity, which was stated to be dependent on ionic sizes and governed by the requirement to maintain charge neutrality in solution.…”
Section: Introductionmentioning
confidence: 99%